Žvižgači - jih znamo zaščititi? - Koželj, Nina (Delavci in delodajalci, 2023)
This abstract provides the reader with the reasoning behind the new Reporting Persons Protection Act which transposes the so-called European Whistleblower Directive (2019/1937/EU) into Slovenian legal system - it briefly introduces the main novelties of the new legislation and examines the most critical and significant issues arising in the initial period of its entry into force.
Keywords: breaches; directives; kršitve; pravo EU; prijavitelji; protection; public disclosures; reporting persons; whistleblowers; zaščita; žvižgači